Investigating the Impact of Teaching Styles on Student Motivation in Middle Schools - Azany, Ocha Alya (Kampret Journal, 2024)
This research investigates the influential connection between teachers' teaching styles and stu-dent learning motivation in middle schools. Recognizing that middle school marks a pivotal stage in students' educational journey, this study employs a mixed methods approach to provide a comprehensive understanding of these relationships. Quantitative analysis reveals significant correlations between specific teaching styles and various dimensions of student motivation. Notably, student-centered teaching approaches exhibit a strong positive correlation with intrinsic motivation, emphasizing the importance of autonomy and engagement in fostering students' inner drive to learn. Conversely, traditional teaching methods show a negative correlation with intrinsic motivation, indicating the need for a reevaluation of these approaches. Qualitative in-sights from student narratives complement the quantitative findings, offering a deeper under-standing of the underlying mechanisms and contextual factors at play. Students consistently express that student-centered teaching methods make learning more engaging, while traditional methods are associated with feelings of monotony and decreased interest. These findings carry practical implications for educational practices and policies. Educators are encouraged to incor-porate more student-centered approaches into their teaching practices to enhance motivation and engagement. Teacher training programs can prioritize the development of skills necessary for effective implementation of these methods. In conclusion, this research contributes to the field of education by emphasizing the importance of pedagogical diversity and aligning teaching styles with students' motivational needs.